The Impact of Asparagus Supply Chain Quality Management: An Empirical Research from Peru - Edgar D. Ramos; Kelsey Provost; Stephanie Calle; Kevin Zavala (International Journal of Supply Chain Management, 2020)
The objective of the article is to show how quality tools help the management of the supply chain in the agricultural sector, in this way quality management of the supply chain will improve operating results in companies that produce asparagus. The company is located in Trujillo, Peru; where the managers of each area were interviewed to determine the practices that will be used in the agribusiness sector. Through the review of the literature, the practices that will be used are supplier relationship management, operations management, and human resources management, the right design and application of these practices will achieve improvements in operational results. The proposed model, Supply Chain Quality Management, is an innovative method that will have a positive impact on the agribusiness supply chain. In addition, quality management in the supply chain is an unusual topic to find in research. Finally, asparagus is a high consumption vegetable and this study provides a great value in increasing economic indicators and competitiveness within the industry.